MAIN EXPORT DIRECTIONS OF EDUCATION SERVICES - Audrey N. Rementsov (Высшее образование в России)
He article describes the main directions of educational services export, discusses the questions of foreign citizens' education expediency from the point of view of the state and university. The article also reveals the reasons why foreign citizens desire to be trained at higher education institutions of Russia. The main directions of the international cooperation of MADI are observed. Specifics of joint educational programs on the example of Vietnamese-Russian Technological University is shown. The special attention is paid to the academic mobility of students and teachers.